Ma'had Aly and the Future of Islamic Higher Education: Bridging Tradition and Modernity in Indonesia’s Islamic Religious College System - Supriyanto, Supriyanto; Waseso, Hendri Purbo; Albar, Mawi Husni; Zain, Muhammad Fuad; Husnayain, Faizul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The issuance of PMA No. 71 of 2015, later revised as PMA No. 32 of 2020, formally positioned Ma’had Aly within Indonesia’s pesantren-based higher education system. This policy marked a significant transformation by integrating traditional Islamic scholarship with formal academic standards under the Islamic Religious Higher Education (PTKI) framework. The study aims to analyse the management dynamics, educational quality, and strategic role of Ma’had Aly in strengthening the national Islamic higher education ecosystem. Employing a qualitative phenomenological approach, data were collected through interviews, focus group discussions, and direct observations at three leading Ma’had Aly institutions: Salafiyah Syafi’iyah Situbondo, Hasyim Asy’ari Tebuireng, and Iqna Ath Tholibin Rembang. The findings indicate that Ma’had Aly remains structurally dependent on the traditional pesantren model, where kiai hold central authority in governance and academic orientation. Despite the strength of classical Islamic pedagogy, which uses methods such as sorogan and bandongan, graduates often face limitations in professional and research skills compared to PTKI students. The study highlights the strategic potential of Ma’had Aly as a bridge between classical Islamic learning and modern higher education. Integrating practical competencies, research capacity, and institutional collaboration with PTKI is essential to enhance its academic relevance and societal impact, ensuring Ma’had Aly contributes effectively to the development of Indonesia’s Islamic intellectual landscape.